Bears in Human-Modified Landscapes: The Case Studies of the Cantabrian, Apennine, and Pindos Mountains - Penteriani, Vincenzo; Karamanlidis, Alexandros A.; Ordiz, Andrés; Ciucci, Paolo; Boitani, Luigi; Bertorelle, Giorgio; Zarzo-Arias, Alejandra; Bombieri, Giulia; González-Bernardo, Enrique; Morini, Paola; Pinchera, Francesco; Fernández, Néstor; et al. (Cambridge University Press, 2020)
Edited by Vincenzo Penteriani and Mario Melletti.-- Part III - Human–Bear Coexistence.-- This material has been published in "Bears of the World. Ecology, Conservation and Management" by / edited by Vincenzo Penteriani and Mario Melletti / Cambridge University Press. This version is free to view and download for personal use only. Not for re-distribution, re-sale or use in derivative works. Brown bears Ursus arctos were historically persecuted and almost eradicated from southern Europe in the twentieth century as a result of hunting and direct persecution. The effects of human-induced mortality were exacerbated by other threats, such as habitat loss and fragmentation, due to the expansion of human populations. As a result, nowadays there are only small fragmented populations of bears in southern Europe. Brown bears in the Cantabrian (north-western Spain), Apennine (central Italy), and Pindos (north-western Greece) mountains represent three examples of small and threatened bear populations in human-modified landscapes. Most of their range is characterized by high human densities, widespread agricultural activities, livestock raising and urban development, connected by dense networks of transport infrastructures. This has resulted in a reduction of continuous habitat suitable for the species. Here, we summarize the past and present histories and fates of these three populations as examples on how the coexistence of bears and people in human-modified landscapes can take different turns depending on human attitudes.